2011
DOI: 10.1210/me.2010-0340
|View full text |Cite
|
Sign up to set email alerts
|

ROS Signaling by NOX4 Drives Fibroblast-to-Myofibroblast Differentiation in the Diseased Prostatic Stroma

Abstract: Stromal remodeling, in particular fibroblast-to-myofibroblast differentiation, is a hallmark of benign prostatic hyperplasia (BPH) and solid tumors, including prostate cancer (PCa). Increased local production of TGFβ1 is considered the inducing stimulus. Given that stromal remodeling actively promotes BPH/PCa development, there is considerable interest in developing stromal-targeted therapies. Microarray and quantitative PCR analysis of primary human prostatic stromal cells induced to undergo fibroblast-to-myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
147
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 56 publications
12
147
1
Order By: Relevance
“…Similar results were observed in other human fibroblast strains including GM21, LF1, and WI38 cells (Supporting Information Figure S3a). The great majority of cells with prominent α‐SMA expression also displayed discrete DDR foci (over 95%; Figure 3a), suggesting a causal link between DDR induction and myofibroblast transdifferentiation, as reported previously (Dimitrijevic‐Bussod, Balzaretti‐Maggi, & Gadbois, 1999; Mellone et al, 2016; Sampson et al, 2011). However, since not all cells with DDR foci expressed high levels of α‐SMA in stress fibers (Supporting Information Figure S3d), our data also suggested that activation of the DDR alone is not sufficient for myofibroblast transdifferentiation and that other factors, such as timing of DDR induction or long‐term persistence of the DDR, are critical for activating the transdifferentiation program.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Similar results were observed in other human fibroblast strains including GM21, LF1, and WI38 cells (Supporting Information Figure S3a). The great majority of cells with prominent α‐SMA expression also displayed discrete DDR foci (over 95%; Figure 3a), suggesting a causal link between DDR induction and myofibroblast transdifferentiation, as reported previously (Dimitrijevic‐Bussod, Balzaretti‐Maggi, & Gadbois, 1999; Mellone et al, 2016; Sampson et al, 2011). However, since not all cells with DDR foci expressed high levels of α‐SMA in stress fibers (Supporting Information Figure S3d), our data also suggested that activation of the DDR alone is not sufficient for myofibroblast transdifferentiation and that other factors, such as timing of DDR induction or long‐term persistence of the DDR, are critical for activating the transdifferentiation program.…”
Section: Resultssupporting
confidence: 83%
“…TGF‐β1 stimulates the production of ROS by promoting expression of NADPH oxidase‐4 (NOX‐4) in a SMAD3‐dependent manner (Hecker et al, 2009; Jiang, Liu, Dusting, & Chan, 2014; Sampson et al, 2011). While TGF‐β1‐induced myofibroblast transdifferentiation involves the production of such ROS, the mechanisms how these reactive molecules facilitate transdifferentiation are still obscure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA isolation, cDNA synthesis and qPCR using Taqman ® gene expression assays were performed as described 18, 22. TaqMan ® gene expression assays (Applied Biosystems, Vienna, Austria) are listed in Supporting Information, Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…ROS play a central role in fibroblast activation 17. In particular, we previously demonstrated a pivotal function of Nox4‐derived ROS during TGFβ1‐induced activation of prostate fibroblasts most likely via redox‐dependent phosphorylation of c‐Jun N‐terminal kinase (JNK) 18. More recently, we and others showed that Nox4 expression is higher in PCa patients that experience biochemical relapse following radical prostatectomy and in patients with decreased PCa‐specific survival 19, 20.…”
mentioning
confidence: 98%